2007
DOI: 10.1074/jbc.m707547200
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer Drugs Up-regulate HspBP1 and Thereby Antagonize the Prosurvival Function of Hsp70 in Tumor Cells

Abstract: The 70-kDa heat shock protein (Hsp70) is up-regulated in a wide variety of tumor cell types and contributes to the resistance of these cells to the induction of cell death by anticancer drugs. Hsp70 binding protein 1 (HspBP1) modulates the activity of Hsp70 but its biological significance has remained unclear. We have now examined whether HspBP1 might interfere with the prosurvival function of Hsp70, which is mediated, at least in part, by inhibition of the death-associated permeabilization of lysosomal membra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 36 publications
2
36
0
Order By: Relevance
“…Cells were fixed with methanol at -20ºC and stained with antibodies to Asp 175 -cleaved caspase-3 (1/100 dilution) and Alexa Fluor 488-conjugated secondary antibodies (1/200 dilution, Molecular Probes) [15]. The appearance of phosphatidylserine on the extracellular side of the plasma membrane and membrane permeability were evaluated by staining with annexin V and propidium iodide, respectively, with the use of an Annexin-V-Fluos staining kit (Roche Diagnostics).…”
Section: Methodsmentioning
confidence: 99%
“…Cells were fixed with methanol at -20ºC and stained with antibodies to Asp 175 -cleaved caspase-3 (1/100 dilution) and Alexa Fluor 488-conjugated secondary antibodies (1/200 dilution, Molecular Probes) [15]. The appearance of phosphatidylserine on the extracellular side of the plasma membrane and membrane permeability were evaluated by staining with annexin V and propidium iodide, respectively, with the use of an Annexin-V-Fluos staining kit (Roche Diagnostics).…”
Section: Methodsmentioning
confidence: 99%
“…Recently it has been found that binding of HspBP1 to Hsp70 prevents inhibition of cathepsin-dependent death of tumor cells. The cells with a high HspBP1/Hsp70 molar ratio possess greater sensitivity to antitumor drugs than the cells with low values of this ratio (31).…”
Section: Discussionmentioning
confidence: 99%
“…Immunoblot Analysis-Cell lysates were prepared and subjected to immunoblot analysis as described (23,24). Immune complexes were visualized with enhanced chemiluminescence reagents (GE Healthcare).…”
Section: Methodsmentioning
confidence: 99%